Inflammation in Steatotic Liver Diseases: Pathogenesis and Therapeutic Targets - Qian, Shengying; Wang, Xiaolin; Chen, Yingfen; Zai, Qiuhong; He, Yong (Seminars in Liver Disease, 2024)
Alcohol-related liver disease (ALD) and metabolic dysfunction-associated steatotic liver disease (MASLD), two main types of steatotic liver disease (SLDs), are characterized by a wide spectrum of several different liver disorders, including simple steatosis, steatohepatitis, cirrhosis, and hepatocellular carcinoma. Multiple immune cell-mediated inflammatory responses not only orchestrate the killing and removal of infected/damaged cells but also exacerbate the development of SLDs when excessive or persistent inflammation occurs. In recent years, single-cell and spatial transcriptome analyses have revealed the heterogeneity of liver-infiltrated immune cells in ALD and MASLD, revealing a new immunopathological picture of SLDs. In this review, we will emphasize the roles of several key immune cells in the pathogenesis of ALD and MASLD and discuss inflammation-based approaches for effective SLD intervention. In conclusion, the study of immunological mechanisms, especially highly specific immune cell population functions, may provide novel therapeutic opportunities for this life-threatening disease.
Keywords: ALD; MASLD; macrophages; neutrophils; single-cell RNA sequencing